2006
DOI: 10.4304/jcp.1.6.1-10
|View full text |Cite
|
Sign up to set email alerts
|

Compression of Short Text on Embedded Systems

Abstract: Abstract-The paper details a scheme for lossless compression of short data series larger than 50 Bytes. The method uses arithmetic coding and context modeling with a low-complexity data model. A data model that takes 32 kBytes of RAM already cuts the data size in half. The compression scheme just takes a few pages of source code, is scalable in memory size, and may be useful in sensor or cellular networks to spare bandwidth. As we demonstrate the method allows for battery savings when applied to mobile phones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…For each form, we took 20 samples of the gateway power consumption using gnome-power-statistics, showing that a mean value of 21.42W and 21.03W were consumed by the first and second form, respectively. In this way, the power that can be consumed by performing the compression is mitigated by the gains of using less power to send less information, particularly over the wireless medium, as is substantiated by [17].…”
Section: ) Compression Energy Consumptionmentioning
confidence: 93%
“…For each form, we took 20 samples of the gateway power consumption using gnome-power-statistics, showing that a mean value of 21.42W and 21.03W were consumed by the first and second form, respectively. In this way, the power that can be consumed by performing the compression is mitigated by the gains of using less power to send less information, particularly over the wireless medium, as is substantiated by [17].…”
Section: ) Compression Energy Consumptionmentioning
confidence: 93%
“…Most of the work is designed for compressing large size text and does not consider devices with limited resources. The researchers of (Rein et al, 2006a) indicated that many of the well known compression require memory from 0.5 to more than 100 Mbyte. On the other hand, most of the sensor networks' data compression techniques use statistical correlations between the typically larger data of multiple sensors as they all observe the same phenomenon which make them unsuitable for text compression.…”
Section: Methodsmentioning
confidence: 99%
“…These algorithms are based on the idea of replacing the strings in the text with a pointer to where they have occurred earlier in the text. This family of algorithms are generally derived from one of the two approaches namely LZ77 and LZ78, respectively (Rein et al, 2006a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations